Cortical developmental abnormalities in logopenic variant primary progressive aphasia with dyslexia. Issue 1 (23rd October 2019) - Miller, Zachary A; Spina, Salvatore; Pakvasa, Mikhail; Rosenberg, Lynne; Watson, Christa; Mandelli, Maria Luisa; Paredes, Mercedes F; Joie, Renaud La; Rabinovici, Gil D; Rosen, Howard J; Grinberg, Lea T; Huang, Eric J; et al.
Abstract: An increased prevalence of dyslexia has been observed in individuals diagnosed with primary progressive aphasia, most notably the logopenic variant primary progressive aphasia. The underlying pathology most commonly associated with logopenic variant primary progressive aphasia is Alzheimer's disease. In this clinical case report series, we describe the neuropathological findings of three patients with logopenic variant primary progressive aphasia and developmental dyslexia, each demonstrating a pattern of cerebrocortical microdysgenesis, reminiscent of findings first reported in dyslexic individuals, alongside expected Alzheimer's disease pathology. Neurodevelopmental and most severe Alzheimer's disease pathological changes overlapped within perisylvian brain regions, areas associated with phonological deficits in both logopenic variant primary progressive aphasia and dyslexia. These three cases with pathological findings support the hypothesis that early-life neurodevelopmental changes might influence later-life susceptibility to neurodegenerative disease and could contribute to non-amnestic, early age-of-onset presentations of Alzheimer's disease. Larger studies investigating neurobiological vulnerability across the lifespan are needed. Abstract : We discovered cortical developmental anomalies, in language-related anatomies, in each of three patients with logopenic variant primary progressive aphasia and developmental dyslexia, reminiscent of findings reported in dyslexic individuals, in association with maximal Alzheimer's disease pathology, providing further evidence linking early-life neurodevelopmental changes with later-life neurodegenerative disease. Graphical Abstract: